Liquidity policies and systemic risk - Tobias Adrian; Nina Boyarchenko (Federal Reserve Bank of New York, 2013)
The growth of wholesale-funded credit intermediation has motivated liquidity regulations. We analyze a dynamic stochastic general equilibrium model in which liquidity and capital regulations interact with the supply of risk-free assets. In the model, the endogenously time-varying tightness of liquidity and capital constraints generates intermediaries' leverage cycle, influencing the pricing of risk and the level of risk in the economy. Our analysis focuses on liquidity policies' implications for household welfare. Within the context of our model, liquidity requirements are preferable to capital requirements, as tightening liquidity requirements lowers the likelihood of systemic distress without impairing consumption growth. In addition, we find that intermediate ranges of risk-free asset supply achieve higher welfare.
Keywords: E02; E32; G00; G28; 330; liquidity regulation; systemic risk; DSGE; financial intermediation